GENOTYPE EXPRESSION OF TRADITIONAL PEAR VARIETY SINEC DEPENDING ON ECOLOGICAL FACTORS - Selamovska, Ana; Elizabeta Miskoska-Milevska, Katerina Nikolic (ECO-CONFERENCE, ECOLOGICAL MOVEMENT OF NOVI SAD, 2022)
This paper presents the results of an examination of the phenological characteristics, pomological properties and chemical composition of the fruits of the traditional pear landrace Sinec in three regions of the Republic of North Macedonia (Kumanovo, Debar and Kriva Palanka). The pear Sinec blooms in mid – April. The fruits ripen from the second decade of August (in Kumanovo and Kriva Palanka) and to the end of August (the Debar region). The landrace pear Sinec forms intermediate small fruits, while larger ones are formed in the region of Kumanovo and Debar. The fruits contain on average 13.9 % soluble dry matters, 13.04 % total sugars and 0.33 % total acids. For all investigated fruit properties are found statistically significant differences except for the content of total acids in the fruit.
Keywords: traditional landrace, flowering, ripening, pomology, chemical traits